Environmental risk of nontuberculous mycobacterial infection: Strategies for advancing methodology. (March 2023) - Mercaldo, Rachel A.; Marshall, Julia E.; Cangelosi, Gerard A.; Donohue, Maura; Falkinham, Joseph O.; Fierer, Noah; French, Joshua P.; Gebert, Matthew J.; Honda, Jennifer R.; Lipner, Ettie M.; Marras, Theodore K.; Morimoto, Kozo; et al.
Abstract: The National Institute of Allergy and Infectious Diseases organized a symposium in June 2022, to facilitate discussion of the environmental risks for nontuberculous mycobacteria exposure and disease. The expert researchers presented recent studies and identified numerous research gaps. This report summarizes the discussion and identifies six major areas of future research related to culture-based and culture independent laboratory methods, alternate culture media and culturing conditions, frameworks for standardized laboratory methods, improved environmental sampling strategies, validation of exposure measures, and availability of high-quality spatiotemporal data.